2015
DOI: 10.1108/tqm-08-2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

Head-teachers ' motivational practices in public secondary schools in Kenya

Abstract: Purpose – The purpose of this paper is to determine the effects of head teachers’ motivational practices on teacher performance in public secondary schools in Kenya. The objectives of the study: to determine the influence of staff recognition; shared leadership by teachers; participation in staff development programmes; and head teachers’ support for the teachers on performance. Design/methodology/approach – The study design was descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…A leader can have a profound and extraordinary effect on subordinates/followers. It is the same with the research conducted by Ocham & Okoth (2015). The research found that the principal strongly influences in increasing teacher performance and how a principal direct his team.…”
Section: Introductionsupporting
confidence: 59%
“…A leader can have a profound and extraordinary effect on subordinates/followers. It is the same with the research conducted by Ocham & Okoth (2015). The research found that the principal strongly influences in increasing teacher performance and how a principal direct his team.…”
Section: Introductionsupporting
confidence: 59%
“…Recognition of teacher accomplishments by administrators can increase teacher motivation to attend professional development and apply what they learn (Ocham & Okoth, ), however administrators often recognize only the hours of professional development completed, not the skills teachers gain through the professional development (Grunwald Associates, ). Digital badges can replace paper certificates and go even further, identifying the skills mastered, how the individual demonstrated competence, and information about the digital badge issuer (Mehta, Hull, Young, & Stoller, ).…”
Section: Introductionmentioning
confidence: 99%
“…The teaching aids are two forms of such as real objects and models ( Morgan, 2012;Tofade et al, 2015). Props have six values in the teaching process [27] : (a) explaining the concept, (b) formulating a concept, (c) train students to get new skills, (d) reinforcement of concepts, (e) train students in problem-solving, (f) train students in measurement, (g) encourage students to think critically and analytically. Existing two sides of using props in teaching and learning process are advantage and disadvantage.…”
Section: Figure Toolsmentioning
confidence: 99%